English language and its relevance in the quality customer service in del Parque Hotel - Castillo Jimenez, Xiomara Estefania (2023)
This case study seeks to answer the following research question: What is the relevance of the English language in the quality of service of the Hotel Del Parque, where the general objective is to determine the relevance of the English language in the quality of service of the 'Hotel Del Parque', through which it will be known if the different national and foreign tourists are fully satisfied with the quality of service provided. The methodology used in the work established the exploratory and documentary approach, qualitative and quantitative research techniques were used since the survey technique was used with a Servqual model establishing 4 dimensions: tangible aspects, reliability, sensitivity, and security. The purpose of which is to determine the different expectations and perceptions of the client, which was applied to people who frequent the Hotel Del Parque and an observation sheet where information was collected to analyze the quality of service provided by the establishment. Once the information was collected, the main results of the survey applied in this case study were obtained, which shows that the majority of the people surveyed consider or totally agree that the establishment has an excellent quality service, however, it is important to emphasize that there is also a not so high level of dissatisfaction with the service in several areas of the Hotel.